Salbutamol Worsens the Autonomic Nervous System Dysfunction of Children With Sickle Cell Disease - Bokov, Plamen; El Jurdi, Houmam; Denjoy, Isabelle; Peiffer, Claudine; Medjahdi, Noria; Holvoet, Laurent; Benkerrou, Malika; Delclaux, Christophe (Frontiers in Physiology, 2020)
Background: Sickle cell disease (SCD) patients with asthma have an increased rate of vaso-occlusive crisis (VOC), acute chest syndrome (ACS) episodes when compared to those without asthma. We hypothesized that either asthma diagnosis or bronchodilator treatment might aggravate SCD via their modulating effect on the autonomic nervous system. Methods: Cross-sectional evaluation of heart rate variability during pulmonary function tests, including salbutamol administration, in children with SCD receiving asthma treatment or not when compared to asthmatic children without SCD matched for ethnicity. Results: SCD children with asthma (n = 30, median age of 12.9 years old) were characterized by a reduced FEV1/FVC ratio, an increased bronchodilator response and a greater incidence of VOC and ACS when compared to SCD children without asthma (n = 30, 12.7 years). Children with asthma without SCD (n = 29, 11.4 years) were characterized by a higher exhaled NO fraction than SCD children. SCD children when compared to non-SCD children, showed reduced heart rate variability (total power, low [LF] and high [HF, vagal tone] frequencies), which was further worsened by salbutamol administration in all the groups: reduction in total power and HF with an increase in LF/HF ratio. After salbutamol, the LF/HF ratio of the SCD children was higher than that of the non-SCD children. The two groups of SCD children were similar, suggesting that asthma diagnosis per se did not modify autonomic nervous system functions. Conclusion: SCD children are characterized by impaired parasympathetic control and sympathetic overactivity that is worsened by salbutamol administration.